2010
DOI: 10.1002/adsc.200900836
|View full text |Cite
|
Sign up to set email alerts
|

The First General and Selective Palladium(II)‐Catalyzed Alkoxycarbonylation of Arylboronates: Interplay among Benzoquinone‐Ligated Palladium(0) Complex, Organoboron, and Alcohol Solvent

Abstract: Methoxycarbonylation of aryl-and alken-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 114 publications
1
37
0
Order By: Relevance
“…Then, concentration was performed under reduced pressure. The crude product obtained was purified by column chromatography (petroleum ether/ ethyl acetate (PE/EA) = 12:1) on silica gel to provide the desired compound Methyl 2-acetylbenzoate (1a): [15] 202.5, 166.6, 142.3, 131.6, 129.6, 129.3, 128.7, 126.1, 61.2, 30.0, 13.6 ppm.…”
Section: Experimental Section Generalp Roceduresmentioning
confidence: 99%
“…Then, concentration was performed under reduced pressure. The crude product obtained was purified by column chromatography (petroleum ether/ ethyl acetate (PE/EA) = 12:1) on silica gel to provide the desired compound Methyl 2-acetylbenzoate (1a): [15] 202.5, 166.6, 142.3, 131.6, 129.6, 129.3, 128.7, 126.1, 61.2, 30.0, 13.6 ppm.…”
Section: Experimental Section Generalp Roceduresmentioning
confidence: 99%
“…An original oxidative transmetalation mechanism, supported by theoretical calculations based on the DFT and MP2 methods, was proposed for the palladium‐catalyzed alkoxycarbonylation of arylboronates 14. The catalytic cycle starts from the Pd 0 complex 10A (Scheme ).…”
Section: Bq As Promoter Of Transmetalationmentioning
confidence: 99%
“…Yamamoto observed that the BQ‐ligated palladium(0) complex Pd(BQ)(cod) (cod = cycloocta‐1,5‐diene) was almost unreactive towards p ‐tolylboronic acid in CDCl 3 , whereas the addition of CD 3 OD led to the formation of the homocoupling product in good yields, together with hydroquinone (Scheme ) 14. This results suggests that methanol acts as a proton donor for the oxidation of Pd 0 in this particular system, hence the transmetalation of the boronic acid leading to the coupling reaction.…”
Section: 1 Regeneration Of Active Pdii Species From Pd0mentioning
confidence: 99%
“…Conversely, Yamamoto et al. described a general and selective palladium‐catalyzed oxidative carbonylation of arylboronates in alcohols 49. In the presence of Pd(OAc) 2 /PPh 3 and BQ, esters were produced from the corresponding arylboronates in good yields at room temperature (Scheme ).…”
Section: Oxidative Carbonylation Of Organometallic Reagentsmentioning
confidence: 99%